Implementasi Putusan Mahkamah Konstitusi Nomor 130/PUU-XIII/2015 Terhadap Proses Penyidikan Tindak Pidana Pencurian Dengan Pemberatan Di Sat Reskrim Polres Kendal - Kusfitono Kusfitono; Umar Ma’ruf; Sri Kusriyah (UNISSULA Semarang, 2020)
The criminal act of theft with a denunciation that occurred at Sat Reskrim Polres Kendal is handled through the process of investigation process in accordance with the revision of Law No. 8 of 1981 on the Criminal Code (KUHAP). The legal basic for the revision of Law Number 8 Year 1981 is the decision of the Constitutional Court Number 130 / PUU-XIII / 2015. This Constitutional Court ruling has changed some of the stages in the pre-prosecution process where previously in the pre-prosecution phase the investigator only gave the Order of letter of notification commencement investigation (LNCI) to the public prosecutor has now been amended and requires the investigator to grant LNCI not only to the public prosecutor but also to the reported and the victim / complainant. However, this Constitutional Court Decision is allegedly a bit of a hindrance and complicate the task of investigators, especially in handling the crime of theft with a denunciation, which with the implementation of this LNCI submission stage especially to the reported, making report easy to eliminate the evidence, influence the witnesses and even reported trying to run self. To overcome this, the action taken by the investigating team is to provide LNCI with several stages while still guided by the decision of the Constitutional Court Number 130 / PUU-XIII / 2015.Keywords: Implementation, Constitutional Court Decision, Theft with Objection